The Relationship between Promotional Media on Cigarette Packaging and the Level of Susceptibility and Seriousness that Students Feel about Quitting Smoking in State High Schools of the Same Level in the City of Kendari - Depu, Anry Hariadhin; Putra Marhanto, Eka Dharma (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: The inclusion of advertisements warning of the dangers of smoking on cigarette packaging raises various views among teenagers, especially among students, who are easily influenced by something new, unique and interesting. Most Indonesian student smokers already have a smoking habit, with 33.9% being male and 2.5% female. This study aims to analyze the relationship between Promotional Media on Cigarette Packaging and the Level of Susceptibility and Seriousness that students feel about quitting smoking in State High Schools of the same level in Kendari City. Method: This research uses a quantitative research design with a cross-sectional research design. The population is all students who smoke in Kendari City High Schools, totaling 104 people. The number of samples using the Lameshow sample formula is 60 people and the sampling technique uses stratified random sampling. Result: This research shows that promotional media on cigarette packaging is related to the vulnerability and seriousness felt by students in quitting smoking in State High Schools of the same level in Kendari City. Conclusion: The government needs to change the promotional media on cigarette packaging, by changing the size of the image to 50% of the width of the front and back of the cigarette pack, accompanied by larger warning writing.